2017
DOI: 10.1002/poc.3749
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted facile synthesis of propargylamine library by robust nitro functionalized cross‐linked polystyrene resin supported Cu NPs

Abstract: In the present investigation, we study catalytic activity of copper nanoparticles stabilized onto a nitro functionalized polystyrene resin (Cu NPs@ Nitro-Resin).The size of stabilized copper nanoparticles was found between 3 and 9 nm. This work reports a cost-effective and sustainable protocol for the synthesis of propargylamines. Herein, we have developed microwave-assisted synthesis of propargylamine from 3 components coupling of aldehyde, alkynes, and amines (A 3 coupling) in truly heterogeneous catalytic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The recovery and recyclability of the immobilized catalyst were explored under the optimized conditions in six consecutive cycles, revealing marginal loss of the catalytic activity, due to the copper leaching from the supporting nitro functionalized polystyrene resin. The principle of the protocol denotes to a green process, whereas the major disadvantage of this methodology is the big amount of copper catalyst used even after considering a certain number of recycling [64] …”
Section: Formation Of Carbon‐carbon Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery and recyclability of the immobilized catalyst were explored under the optimized conditions in six consecutive cycles, revealing marginal loss of the catalytic activity, due to the copper leaching from the supporting nitro functionalized polystyrene resin. The principle of the protocol denotes to a green process, whereas the major disadvantage of this methodology is the big amount of copper catalyst used even after considering a certain number of recycling [64] …”
Section: Formation Of Carbon‐carbon Bondmentioning
confidence: 99%
“…The principle of the protocol denotes to a green process, whereas the major disadvantage of this methodology is the big amount of copper catalyst used even after considering a certain number of recycling. [64] In a similar manner, copper nanoparticles supported on zinc oxide-polythiophene nanocomposite were employed as heterogeneous catalyst in the synthesis of a variety of substituted propargylamine and pyrrolo[1,2-a]quinolines through A 3 and KA 2 coupling reactions. Moderate to high yields were accomplished, irrespective of the substituents on the starting materials, under microwave irradiation settings in ethylene glycol as a recyclable and green solvent.…”
Section: Formation Of Carbon-carbon Bondmentioning
confidence: 99%
“…Kaur et al accomplished the microwave-assisted synthesis of propargylamines using a Cu/Resin, which was composed of copper nanoparticles stabilized onto a nitrofunctionalized polystyrene resin. 27 The one-step, threecomponent coupling reactions of aldehydes, amines, and alkynes with the Cu/Resin catalyst (3.78 mmol%) in toluene Cravotto et al reported microwave-assisted dehydrogenative coupling reactions using palladium nanoparticles supported on a -cyclodextrin crosslinked network (Pd/CCAT). 28 The oxidative cross-coupling reaction between 2-methylthiophene and benzo[d]thiazole with Pd/CCAT at 140 °C (MWI) in -valerolactone, a biomassderived solvent, furnished the product in 95% yield (Scheme 30).…”
Section: Scheme 24 Pd/bc-catalyzed Synthesis Of Xanthones 3 Microwave-assisted Coupling Reactions In Nonpolar Solventsmentioning
confidence: 99%
“…The reaction proceed smoothly using very low catalytic amount (0.1 mol %) of the copper based complex in acetonitrile as solvent (CH 3 CN), the reaction mixture was then heated in a microwave oven at 85 • C for short reaction time (5 min) to generate the propargylamine derivatives in good to excellent yields, Scheme 34. In another study utilizing microwave technology, polystyrene resin supported copper nanoparticles (Cu NPs@Resin) have been developed by Kaur and coworkers for the synthesis of propargylamine derivatives via A 3 coupling reaction of aldehyde, alkynes, and amines [60]. Cu NPs@Resin was used to catalyze the reaction in toluene as solvent.…”
Section: Synthesis Of Propargylaminesmentioning
confidence: 99%